A Heliocentric Journey into Germanys Great Depression - Mark Weder (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2003)
The paper finds empirical evidence on the ripple effect of sunspots on the interwar German economy. It identifies a sequence of negative shocks to expectations for the 1927 to 1932 period. The artificial economy predicts the 1928-1932 depression and a long boom from 1933 onwards. Overall, a tangible fraction of interwar output volatility is attributed for by sunspots.
urn:nbn:de:kobv:11-10050851
Keywords: 330; Wirtschaftskrise; Sunspot; Exogene Konjunkturtheorie; Deutschland